Management Of Creative Economy Based Skills Education Program For Students In Islamic Boarding School: Manajemen Program Pendidikan Keterampilan Berbasis Ekonomi Kreatif untuk Siswa di Pondok Pesantren - Kharis (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2024)
The management of the Creative Economy-Based Student Skills Education Program is a positive effort to realize the goal of Islamic boarding schools to equip students with religious knowledge and general knowledge. In the current era of high competition, students need to be equipped with various skills to be able to compete later, especially in the economic field. The purpose of writing this article is to discuss the theories of management of creative economy-based student skills programs in Islamic boarding schools. The results of the study show that the management of creative economy-based student skills education programs in Islamic boarding schools can be done through: (1) Developed in Islamic boarding school academic programs, (2) Developed in the form of Islamic boarding school extracurricular activities, (3) Developed in the form of communities, (4) Developed in the form of habits, and (5) Developed in the form of seminars and training. The skills programs that can be developed in Islamic boarding schools are: (1) self-skills, (2) academic skills, (3) social skills, and (4) vocational skills. With these efforts, it is hoped that Islamic boarding schools can develop and prepare students' skills to continue their lives after leaving the Islamic boarding school.